2021
DOI: 10.3390/ijms22169094
|View full text |Cite
|
Sign up to set email alerts
|

TRIM25 and DEAD-Box RNA Helicase DDX3X Cooperate to Regulate RIG-I-Mediated Antiviral Immunity

Abstract: The cytoplasmic retinoic acid-inducible gene-I (RIG-I)-like receptors (RLRs) initiate interferon (IFN) production and antiviral gene expression in response to RNA virus infection. Consequently, RLR signalling is tightly regulated by both host and viral factors. Tripartite motif protein 25 (TRIM25) is an E3 ligase that ubiquitinates multiple substrates within the RLR signalling cascade, playing both ubiquitination-dependent and -independent roles in RIG-I-mediated IFN induction. However, additional regulatory r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
(107 reference statements)
0
10
0
Order By: Relevance
“…DDX3X, which is encoded on the X-chromosome, has a role to play in multiple biological functions including innate immunity and the cellular stress response. We and others have previously shown that DDX3X plays a prominent role in enhancing the RLR-mediated type I interferon (IFN) antiviral response by associating with various RLR signaling molecules including TBK1 (TANK-binding kinase I) and IKKε (I-kappa-B kinase-ε) and direct interaction with the IFNB1 promoter ( 39 43 ) ( Figure 1 ). DDX3X also participates in the formation of cytoplasmic stress granules, membraneless cytosolic bodies that form during the cell stress response, as well as during viral infection ( 44 , 45 ).…”
Section: New Players In Nlrp3 Inflammasome Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…DDX3X, which is encoded on the X-chromosome, has a role to play in multiple biological functions including innate immunity and the cellular stress response. We and others have previously shown that DDX3X plays a prominent role in enhancing the RLR-mediated type I interferon (IFN) antiviral response by associating with various RLR signaling molecules including TBK1 (TANK-binding kinase I) and IKKε (I-kappa-B kinase-ε) and direct interaction with the IFNB1 promoter ( 39 43 ) ( Figure 1 ). DDX3X also participates in the formation of cytoplasmic stress granules, membraneless cytosolic bodies that form during the cell stress response, as well as during viral infection ( 44 , 45 ).…”
Section: New Players In Nlrp3 Inflammasome Activationmentioning
confidence: 99%
“…The determination of the DDX3X AKT-phosphorylation site/s would validate these results and potentially highlight a unique DDX3X-targeting site. Likewise, other post-translational modifiers of DDX3X, including tripartite motif protein 25 (TRIM25) ( 39 ) and TANK binding kinase 1 (TBK1) ( 43 ), may influence NLRP3 inflammasome activation but these remain to be explored.…”
Section: Modulating the Nlrp3 Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was found that TRIM25 enhances the antiviral activity of zinc finger antiviral protein (ZAP) with both ubiquitin ligase activity and multimerization ( Li et al, 2017 ; Zheng et al, 2017 ). In addition, TRIM25 ubiquitinates DDX3X (a critical component of TBK1) at K55, and TRIM25 and DDX3X cooperatively enhance type I IFN induction following RIG-I activation ( Soulat et al, 2008 ; Atkinson et al, 2021 ).…”
Section: Viral Antagonization Of Trimsmentioning
confidence: 99%
“…Moreover, the N-terminal domain of NS1 encoded by IBV is responsible for interaction with TRIM25, and this interaction blocks the Lys63-linked ubiquitination of RIG-I ( Jiang et al, 2016 ). Recently, it was found that NS1 disrupts the TRIM25:DDX3X interaction, abrogating both TRIM25-mediated ubiquitination of DDX3X and cooperative activation of the IFNB1 promoter ( Atkinson et al, 2021 ).…”
Section: Viral Antagonization Of Trimsmentioning
confidence: 99%